2020
DOI: 10.1007/s11060-020-03509-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics impacts upon prognosis and clinical management of choroid plexus tumors

Abstract: Purpose Choroid plexus tumors comprise of choroid plexus papilloma (CPP, WHO grade I), atypical choroid plexus papilloma (aCPP, WHO grade II) and choroid plexus carcinoma (CPC, WHO grade III). Molecular events driving the majority of choroid plexus tumors remain poorly understood. Recently, DNA methylation profiling has revealed different epigenetic subgroups. Methods Comprehensive review of epigenetic profiles of choroid plexus tumors in the context of histopathological, genetic, and clinical features. Summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Prior studies have shown that DNA methylation profiling can discriminate between the histological grades of CPTs (ie CPP, aCPP, CPC) often allowing for a more accurate and reproducible means of diagnosis. 4 , 5 , 49 , 50 The methylation class Choroid Plexus Tumor, Pediatric A comprised of mostly histologic CPP or aCPP while class Choroid Plexus Tumor, Pediatric B was enriched with histologic CPCs. 50 In our study, 11 of 12 patients had tumors that clustered with reference class Choroid Plexus Tumor, Pediatric B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that DNA methylation profiling can discriminate between the histological grades of CPTs (ie CPP, aCPP, CPC) often allowing for a more accurate and reproducible means of diagnosis. 4 , 5 , 49 , 50 The methylation class Choroid Plexus Tumor, Pediatric A comprised of mostly histologic CPP or aCPP while class Choroid Plexus Tumor, Pediatric B was enriched with histologic CPCs. 50 In our study, 11 of 12 patients had tumors that clustered with reference class Choroid Plexus Tumor, Pediatric B.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 49 , 50 The methylation class Choroid Plexus Tumor, Pediatric A comprised of mostly histologic CPP or aCPP while class Choroid Plexus Tumor, Pediatric B was enriched with histologic CPCs. 50 In our study, 11 of 12 patients had tumors that clustered with reference class Choroid Plexus Tumor, Pediatric B. The one sample that clustered with subclass A was histologically described to display features of aCPP but judged more compatible with CPC due to mitotic figure counts, Ki-67 and metastatic status.…”
Section: Discussionmentioning
confidence: 99%
“…Int J App Pharm, Vol 13, Issue 5, 2021, 122-131 123 patient identification at risk of recurrence, but also play an important role for the treatment stratification and the patient management [31].…”
Section: E Akahomentioning
confidence: 99%
“…Extracellular activity of CD38 has a wide range of imprecations for NAD+homeostasis in the context of infection, aging and tumor biology [30]. (Thomas et al, 2020) stated that DNA methylation profiling of choroid plexus cancer will aid the understanding of choroid plexus tumor biology, and can not only be used for the…”
Section: Introductionmentioning
confidence: 99%
“…The Publisher regrets that the article by Thomas et al [1], which is part of this Epigenetics of Pediatric Brain Tumors: Clinical Implications colle ction , was published in an earlier issue 148(1):39-45.…”
mentioning
confidence: 99%